Large dentigerous cyst associated to maxillary canine - Bonardi, João Paulo [UNESP]; Gomes-Ferreira, Pedro Henrique Silva [UNESP]; De Freitas Silva, Leonardo [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; De Oliveira Sabrina Ferreira, Danila [UNESP]; Dos Santos Pereira, Rodrigo [UNESP]; Souza, Francisley Ávila [UNESP] (Wolters Kluwer, 2017)
Dentigerous cysts are defined as a cyst originated by separation of the follicle of dental crown of a tooth unerupted. Although most dentigerous cysts are considered developmental cysts, some cases seem to have an inflammatory origin. The aim of this study was to show a case of an 8-year-old patient, male, presenting a lesion in maxilla with large proportions. Computed tomography scans showed a hypodense image, well-defined, associated to unerupted teeth. The case was treated by enucleation of the lesion under local anesthesia. Histopathological examination confirmed the diagnostic suspicious of dentigerous cyst. Currently, 3-year follow-up period showed no signs of recurrence, and it was observed eruption of the teeth associated to the lesion. This case highlights the importance of the association between clinical and radiographic analysis together to the surgical findings, aiming the best treatment for the patient.
Keywords: Biopsy; Dentigerous cyst; Operative; Surgical procedures